Changes in Serum Cytokines May Predict Therapeutic Efficacy of Tofacitinib in Rheumatoid Arthritis - Yuxuan Li; Lin Yuan; Jie Yang; Yue Lei; Hui Zhang; Liping Xia; Hui Shen; Jing Lu (Hindawi Limited, 2019)
Objective. Tofacitinib is a novel therapy for rheumatoid arthritis (RA). The aim of this study was to measure various serum cytokines levels and to explore potential markers predictive of therapeutic efficacy of tofacitinib for RA patients. Methods. Thirty-two patients with RA were given tofacitinib (5 mg bid). Serum cytokines levels of Th1 (IFN-γ), Th2 (IL-6), Th17 (IL-17), Tregs (IL-35), and TNF-α were detected by enzyme-linked immunosorbent assays. Results. Disease activity was significantly decreased as early as week 4 after tofacitinib treatment. Serum IL-35 levels were significantly increased and serum levels of TNF-α, IL-17, IL-6, and IFN-γ were significantly reduced in response to tofacitinib since week 4. Conclusions. After treatment with tofacitinib, RA patients may benefit from monitoring of disease activity as early as week 4. IL-35 also might be a predictive indicator of the disease activity and drug efficacy. Meanwhile, tofacitinib might be CS-sparing in RA.